Implementación de la contabilidad comercial en la empresa del señor Cumbicus Rojas Olmer Eden, de la ciudad de Cariamanga, provincia de Loja, periodo noviembre 2015 - Montero Abad, Adriana Esmeralda del Cisne (2017)
This research paper entitled: "IMPLEMENTATION OF THE COMMERCIAL COMPANY ACCOUNTING MR. CUMBICUS ROJAS OLMER EDEN, CARIAMANGA CITY, PROVINCE, OF LOJA, PERIOD NOVEMBER - 2015", it executed according to the information provided by the owner of the company, knowing the needs and weaknesses of the same; in order to provide both theoretical and practical knowledge to help the owner to keep better control over economic movements of your business. It was also developed for the purpose of obtaining the engineering degree in Accounting and Auditing, CPA. The objectives that guided the implementation of accounting in the company of Mr. Cumbicus Rojas Olmer Eden, from initial inventory leading to the development to the initial situation with real, actual values and obligations in which it was fulfilled the company also plans and manual account that served as support for the proper conduct of the accounting process, which resulted in the issuance of the financial statements and the Income Statement, Statement of Financial Position and Cash Flow Statement was designed. Once the investigative work is completed, the owner, the results of all the movements of your business with the implementation of accounting and in turn recommended to continue applying this process, which will enable a successful progress and improving trade reported.